FORMATION OF SOYBEAN (GLYCINE MAX (L.) MERR.) PRODUCTIVITY ON SOD-PODZOLIC SOIL UNDER DIFFERENT DOSES OF FERTILIZERS AND MELIORANTS - Polovyy, Володимир; Ященко, Людмила; Rovna, Галина (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
Soybean occupies a leading place in world agriculture. Among a number of agrotechnical measures that ensure the varieties potential realization, the fertilization system has an important place. Taking into account the expansion of its cultivation areas in the Western Polissia zone, a study was conducted on the formation of individual productivity indicators of soybean plants as an integral indicator of the action of various doses of fertilizers and meliorants on sod-podzolic soil. Research methods: field, biometric, statistical. The research was conducted in a stationary field experiment. It was established that the application of fertilizers against the background of chemical ameliorants stabilized the interval of plant height with a coefficient of variation of V<5%. Plant survival was on average 80.7–80.9% in variants N55P20K50 and N65P50K75 on the background of 1.0 Hh and N45P60K60 on the background of 1.5 Hh CaMg(CO3)2, which is more than the control by 6.5–9.0 %. Fertilization against the background of ameliorants helped to increase the individual productivity of plants. It was the highest in the variant N65P50K75 + S40 + microfertilizer (twice) against a background of 1.0 doses of Hh СaMg(CO3)2: the number of beans 13.7 pcs., the number of grains per plant 30.1 pcs., the weight of 1000 grains 166.6 g, the mass of grain from the plant is 5.02 g. However, these values were not significant at p≤0.05 compared to the dose of N55P20K50 under other identical conditions. Regulation of soybean structure indicators due to fertilization against the background of ameliorants led to higher seed productivity of the crop. On average, in 2021-2022, the highest seed yield of 2.48 and 2.60 t ha-1 was provided by doses of N55P20K50 and N65P50K75 with the addition of S40 + microfertilizer against a background of 1.0 Hh of a dose of CaMg(CO3)2. It was established that the application of nitrogen fertilizers in the dose of N55 with the addition of S40 + microfertilizer (twice) on the background of 1.0 dose of CaMg(CO3)2 increased the yield by 58.9% to the control and by 15.6% to the background, but it was significantly inferior to the options complete mineral nutrition.